Social Benefits and Economic Security - Vaslavskaya, Irina Yuryevna; Koshkina, Irina Alexandrovna; Fattakhova, Alfiya Ruslanovna; Khakimova, Sabina Damirovna (International Journal of Economics and Financial Issues, 2015)
Questions concerning economic security are important in any economic situation, and in the context of the strongest terms external political and economic pressure on the Russian Federation, the application of sanctions in many areas of cooperation with Western countries are particularly relevant. The system of economic security at the meso and macro levels is different from the economic security enterprise and it should include some structural elements reflecting the relation of territory economic security and state through the public good category. The main purpose of the work was to identify the relationship between economic factors and social security benefits, their production and consumption. The article also presents the conceptual construct of the theory public goods and economic security. It is shown that the economic security system should include public goods as one of the categories system of economic security and take into account the effect of changes in their production and consumption to changes in the economic security territory. Keywords: public good, production, economic security, value, economic policy, industrial policy JEL Classifications: J18, H75